HUBUNGAN RELIGIUSITAS DENGAN PERILAKU BELAJAR MAHASISWA FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - ., Nuryamin (Inspiratif Pendidikan, 2023)
This study aims to determine the level of religiosity and its relationship with student learning behavior. This research is a correlational quantitative research involving 98 respondents from 8 departments. The statistical test used to test the hypothesis with Rank Spearmen. Student religiosity formed from belief, ritual, mystical, intellectual, and social aspects is in the very religious category and student learning behavior (habits, skills, observation, associative, rational-critical, attitude, inhibition and appreciation) is included in the high category. Based on simple correlation analysis, it can be concluded that the level of student religiosity has a positive effect on student learning behavior. This can be seen from the correlation coefficient of the level of religiosity of 0.662. And based on the R square value of 0.438 indicates that the variable level of religiosity gives a positive correlation to student learning behavior.